Ulk4, a Newly Discovered Susceptibility Gene for Schizophrenia, Regulates Corticogenesis in Mice - Hu, Ling; Chen, Yi; Yang, Cui-Ping; Huang, Ying; Song, Ning-Ning; Chen, Jia-Yin; Sun, Yu-Ling; Ding, Yu-Qiang; Lang, Bing (Frontiers in Cell and Developmental Biology, 2021)
Schizophrenia (SCZ) is a chronic and severe mental disease which affects around 1% population. The precise aetiology of SCZ still remains largely unknown and no conclusive mechanisms are firmly established. Recent advances in epidemiological and clinical investigation support an overwhelmingly strong neurodevelopmental origin for SCZ. Here, we demonstrated that Unc-51-like kinase 4 (Ulk4), a novel risk factor for major mental disorders including schizophrenia, is involved in the corticogenesis. Deletion of Ulk4 in mice led to significantly thinner layers of II-III and V in the cerebral cortex, which was confirmed in conditional Ulk4 deletion mice achieved by Cre-loxp strategy. This abnormality might be caused by decreased intermediate neural progenitors and increased apoptosis. Thus, our data suggest that Ulk4 manipulates behaviors of neural progenitors during brain development and when functionally defective, leads to reduction of specific cortical layers. This anomaly may increase predisposition to a range of neurodevelopmental disorders including SCZ.